Simultaneous Determination of Sulfonamides Antibiotics in Environmental Water and Seafood Samples Using Ultrasonic-Assisted Dispersive Liquid-Liquid Microextraction Coupled with High Performance Liquid Chromatography - Yixiao Wang; Jinhua Li; Ling Ji; Lingxin Chen (Molecules, 2022)
The residues and abuse of antibiotics have seriously endangered ecological balance and human health; meanwhile, antibiotics determination is very difficult because of their low levels and multiple categories in complicated matrices. Appropriate sample pretreatment is usually imperative to enrich (ultra)trace antibiotics and eliminate matrix interference prior to chromatographic analysis. Dispersive liquid-liquid microextraction (DLLME) has become an ideal pretreatment technique owing to its simplicity, effectiveness, low-consumption, etc. In this work, an ultrasonic-assisted DLLME (UA-DLLME) was developed for the simultaneous extraction of seven sulfonamides (SAs) antibiotics in environmental water and seafood samples coupled with HPLC-DAD determination. Several parameters affecting UA-DLLME efficiency were systematically optimized, and consequently the SAs were separated and detected within 14.5 min. The obtained limits of detection (LODs) and limits of quantification (LOQs) ranged from 0.7–7.8 μg/L and 2.4–26.0 μg/L for three water samples (seawater, aquaculture wastewater and lake water) and two seafood samples (pomfrets and shrimps). High recoveries (80.0–116.0%) with low relative standard deviations (0.1–8.1%) were achieved for all the tested samples at three spiked levels. Notably, sulfadimethoxine was found at 24.49 μg/L in one seawater sample. The facile, robust and benign DLLME-HPLC method demonstrated promising perspectives for multiresidue analysis of antibiotics.